2022
DOI: 10.3390/ijms231911134
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Mechanical Approach in Biomedicine: Benefits, Challenges, and Future Perspectives

Abstract: The magneto-mechanical approach is a powerful technique used in many different applications in biomedicine, including remote control enzyme activity, cell receptors, cancer-selective treatments, mechanically-activated drug releases, etc. This approach is based on the use of a combination of magnetic nanoparticles and external magnetic fields that have led to the movement of such nanoparticles with torques and forces (enough to change the conformation of biomolecules or even break weak chemical bonds). However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 119 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…Interestingly, our data show that the magnetomechanical effect from the rod-shaped NPs was already achieved at a concentration of 6 μg•mL −1 after 1 h of LF-AMF exposure (f = 31 Hz, B = 100 mT), while no cytotoxic effects at the same concentration of NPs were observed for untreated cells. This value of NP concentration, resulting in decreasing cell viability in magnetomechanical experiments, is the order of magnitude less than the similar concentration of spherical NPs, previously mentioned in other works, 53 while the enhanced magnetomechanical effect may be the result of high shape anisotropy of rod-shaped CF@NaOH/ ann NPs. With an increase in the concentration of NPs, they themselves begin to show a weak toxic effect.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, our data show that the magnetomechanical effect from the rod-shaped NPs was already achieved at a concentration of 6 μg•mL −1 after 1 h of LF-AMF exposure (f = 31 Hz, B = 100 mT), while no cytotoxic effects at the same concentration of NPs were observed for untreated cells. This value of NP concentration, resulting in decreasing cell viability in magnetomechanical experiments, is the order of magnitude less than the similar concentration of spherical NPs, previously mentioned in other works, 53 while the enhanced magnetomechanical effect may be the result of high shape anisotropy of rod-shaped CF@NaOH/ ann NPs. With an increase in the concentration of NPs, they themselves begin to show a weak toxic effect.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The rod-shaped morphology and high value of the anisotropy energy barrier K eff V NP of CF@NaOH/ann NPs also favor their application as transductors of the energy of the low-frequency alternating magnetic fields into mechanical energy, which is applied in remote magnetomechanical actuation of biomolecules and cancer cell destruction . Noninvasive nature and deep tissue penetration of magnetic fields make magnetomechanical actuation stand out among other stimulation techniques.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[39][40][41][42] This effect is called magnetomechanical therapy. [43][44][45] Several studies have already demonstrated that nano-and micrometre-sized particles with different shapes induce the death of cancer cells upon low-frequency alternating or rotating magnetic fields. [46][47][48][49][50][51] However, the study 52 reports an insignificant effect of the magnetomechanical effect on cell viability with the application of micrometre particles, while nanoparticles increase the destroyed cell rate to 30% among cells with internalized particles.…”
Section: Introductionmentioning
confidence: 99%